Propolis immunomodulatory activity on TLR-2 and TLR-4 expression by chronically stressed mice - Orsatti, Claudio Lera [UNESP]; Sforcin, Jose Mauricio [UNESP] (Taylor & Francis Ltd, 2012)
Our group has been investigating the immunomodulatory activity of propolis in stressed mice. In this work, we wish to report the action of propolis in chronically stressed mice, assessing the Toll-like receptor (TLR2 and TLR-4) expression by spleen cells and corticosterone levels as a stress indicator. Male C57BL/6 mice were divided into four groups: G1 was considered the control; G2 was treated with propolis (200mg kg(-1)); G3 was submitted to restraint stress for 14 days; and G4 was treated with propolis and immediately submitted to stress. After sacrifice, spleens were removed and TLR-2 and TLR-4 gene expression was analysed. TLR-2 and TLR-4 expression was increased in propolis-treated mice, and propolis administration to stressed mice prevented the inhibition of TLR-2 and TLR-4 expression. No differences were seen in the corticosterone levels among the groups. Propolis exerted an immunomodulatory action in chronically stressed mice, upregulating TLR-2 and TLR-4 mRNA expression, contributing to the recognition of microorganisms and favouring the initial steps of the immune response during stress.
Keywords: propolis; stress; Toll-like receptors